ChemInform Abstract: Accessing 2, 1‐Borazaronaphthols: Self‐Arylation of 1‐Alkyl‐2‐aryl‐3‐bromo‐2, 1‐borazaronaphthalenes. Issue 10 (March 2015) - Molander, Gary A.; Wisniewski, Steven R.
Abstract The Pd‐catalyzed self‐arylation of 3‐bromo‐2, 1‐borazaronaphthalenes (I) and (III) is developed to yield arylated B‐hydroxycompounds (II) and (V) together with the anhydrides (IV).